2020
DOI: 10.1111/dpr.12455
|View full text |Cite
|
Sign up to set email alerts
|

Public spending on agricultural productivity and rural commercialization: A comparison of impacts using an economy‐wide approach

Abstract: Motivation: Many developing countries have identified a set of strategic objectives and a longlist of investment areas to promote agricultural production and ensure food security. However, most of these countries lack the financial and technical capacity to execute all of the strategic objectives and investment areas, calling for a robust comparison of their effects. Purpose: Taking the case of Ethiopia as an example, this study employs an economy-wide model and assesses the relative efficiency of alternative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Aragie, E applied economic modeling in economics to assess the relative efficiency of alternative investment choices for agricultural performance and household welfare. To explain the linkages, as well as the direct and indirect impacts of alternative public expenditure policies, the study used a general equilibrium model of Ethiopia calibrated according to a well-decomposed socio-accounting matrix representing the structure of the economy in the year 2010 [10]. Gurnovich, T. The innovation and investment processes in the agricultural economy were studied by using system analysis methods taking into account the manifestations of the trend of digitization of the agroindustry.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Aragie, E applied economic modeling in economics to assess the relative efficiency of alternative investment choices for agricultural performance and household welfare. To explain the linkages, as well as the direct and indirect impacts of alternative public expenditure policies, the study used a general equilibrium model of Ethiopia calibrated according to a well-decomposed socio-accounting matrix representing the structure of the economy in the year 2010 [10]. Gurnovich, T. The innovation and investment processes in the agricultural economy were studied by using system analysis methods taking into account the manifestations of the trend of digitization of the agroindustry.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Empirical evidence has shown that certain smallholder agricultural subsidies can significantly enhance productivity. For example, Aragie and Balié (2021) discovered that subsidies for inputs and irrigation development were more effective in improving farmers' productivity than subsidies for infrastructure development. Martey et al (2019) reported that fertilizer subsidy programs resulted in a substantial 55% increase in land productivity, primarily due to the increased use of mineral fertilizers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, offering higher subsidy rates for crop insurance can incentivize greater participation among farmers, ultimately leading to increased productivity (Connor & Katchova 2020). Productivity in these studies is often measured through indicators such as output (Aragie & Balié 2021;Martey et al 2019) and crop yields (Connor & Katchova 2020;Fearon et al 2015;Holden & Lunduka 2010;Woittiez et al 2018). In the context of this study on oil palm plantations, many scholars have chosen the FFB as a proxy for productivity, as observed in works by Ismiasih (2018), Juyjaeng et al (2018), andPuruhito et al (2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation